2008
DOI: 10.1111/j.1524-475x.2008.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired wound healing in an acute diabetic pig model and the effects of local hyperglycemia

Abstract: Diabetic wounds result in significant morbidity, prolonged hospitalization, and enormous health-care expenses. Pigs have been shown to have wound healing resembling that in humans. The aim of this study was to develop a large-animal model for diabetic wound healing. Diabetes was induced by streptozotocin injection in Yorkshire pigs. Full-thickness wounds were created and dressed with a sealed chamber. Nondiabetic pigs with or without high glucose wound fluid concentration served as controls. Glucose concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
102
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 40 publications
(37 reference statements)
5
102
1
1
Order By: Relevance
“…In a previous study, we could show that wounds in a nondiabetic pig showed 96% re-epithelialization by day 12 after wounding using the same animal model [7]. Thus, we were able to significantly enhance diabetes impaired wound healing close to the normal (nondiabetic) level of reepithelialization in the present study.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In a previous study, we could show that wounds in a nondiabetic pig showed 96% re-epithelialization by day 12 after wounding using the same animal model [7]. Thus, we were able to significantly enhance diabetes impaired wound healing close to the normal (nondiabetic) level of reepithelialization in the present study.…”
Section: Discussionsupporting
confidence: 73%
“…On the other hand, IGF-1 showed proliferative effects on keratinocytes and fibroblasts in vitro [6]. In our diabetic wound-healing model, we confirmed these data: Expression of human IGF (hIGF)-1 in diabetic wounds was markedly reduced compared to nondiabetic wounds [7]. These findings led us to the hypothesis that enhanced IGF-1 expression in diabetic wounds can alter wound healing.…”
Section: Introductionsupporting
confidence: 84%
“…There is a compromise of the chemotaxis, phagocytosis and bactericide capacity 9,27 , reduced expression of shock proteins 39 , lower antioxidant production and increased production of oxygen free radicals 40,41 during the initial phase of the process, which adversely affects healing. Furthermore, there is depletion of growth factors [5][6][7][8]11,12 , increased levels of glucocorticoids 42 , loss of cellular proliferation and increased regulation of apoptosis 10,11,[43][44][45] , characteristics of the later phase of healing in diabetics, which results in poor granulation tissue formation 11 . FranzĂ©n and Roberg 46 , studying healing in diabetic rats, showed that fibroblasts have a lower number of cytoplasmatic protrusions with lower surface density of the plasmatic membrane, which indicates the reduced motility of these cells, a condition linked to reduced healing.…”
Section: Discussionmentioning
confidence: 99%
“…FranzĂ©n and Roberg 46 , studying healing in diabetic rats, showed that fibroblasts have a lower number of cytoplasmatic protrusions with lower surface density of the plasmatic membrane, which indicates the reduced motility of these cells, a condition linked to reduced healing. Velander et al 12 , working with pigs that had diabetes induced by streptozotocin, observed a significant fall of the levels of TGF-ß and IGF-1 on the seventh day, the latter being an important stimulator of the proliferation of keratinocytes and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation